OPTIMALISASI PERUMUSAN TUJUAN PEMBELAJARAN PAI MELALUI INTEGRASI PRINSIP ABCD DAN TAKSONOMI BLOOM: SEBUAH TINJAUAN TEORETIS - Anisah Fadhila Azri; Amisah; Siti Khairiah; Nyai Lailatun Naza (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
Islamic Religious Education is a key foundation in the development of an individual’s character and morals. To achieve success in learning, a learning environment with measurable, clear, and well-defined learning objectives is essential. The purpose of this study is to examine the application of the ABCD principles (Audience, Behavior, Condition, Degree) and Bloom’s Taxonomy in formulating learning objectives for Islamic Religious Education. The research method employed in this study is qualitative, utilizing a literature review approach through descriptive analysis of various relevant sources. The results indicate that many educators still formulate Islamic Religious Education learning objectives that are too vague, making them difficult to measure and evaluate. It can be concluded that the formulation of measurable Islamic Religious Education learning objectives can be optimized by integrating the ABCD principles with Bloom’s Taxonomy. Furthermore, the application of these two concepts is highly recommended in formulating learning objectives to help teachers determine more efficient and concrete teaching methods and evaluation approaches. Thus, optimizing the formulation of learning objectives by integrating the ABCD principles and Bloom’s Taxonomy can improve the quality of learning.